Crystal structure, synthesis and characterization of different chromium-based two-dimensional compounds - Maria Hasan; Huy Q. Ta; Sami Ullah; Xiaoqin Yang; Jingping Luo; Alicja Bachmatiuk; Thomas Gemming; Barbara Trzebicka; Azhar Mahmood; Mengqi Zeng; Lei Fu; Lijun Liu; et al. (Arabian Journal of Chemistry, 2023)
The field of two dimensional (2D) materials experienced a surge of discoveries after the isolation of graphene. Among these, the transition metal compounds of Molybdenum and tungsten have been the most extensively studied materials after graphene. More recently, their group member chromium has only recently come to the limelight after the discovery of its exciting magnetic properties. As such the body of work surrounding 2D chromium-based materials is growing. Here, we present an up-to-date summary of the chromium 2D materials showing the latest advances in their experimental synthesis, characterization and the applications of 2D Chromium-based compounds. Finally, we conclude with a perspective on the future of 2D chromium-based materials. We believe that this study will be helpful to understand the field of chromium-based 2D compounds.